Two-dimensional magnetic monopole gas in an oxide heterostructure - L. Miao (Nature Portfolio, 2020)
Heterostructure interfaces have physical properties distinct from bulk materials, providing the basis for many electronic devices. Miao et al. propose a spin ice heterostructure that can host a two-dimensional gas of emergent magnetic monopoles with a net magnetic charge.